2013
DOI: 10.7461/jcen.2013.15.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Left Atrial Enlargement and Stroke Subtypes in Acute Ischemic Stroke Patients

Abstract: ObjectiveIncreased atrial size is frequently seen in ischemic stroke patients in clinical practice. There is controversy about whether left atrial enlargement (LAE) should be regarded as a risk factor for cerebral infarction. We investigated the association between indexed left atrial volume (LAVI) and conventional stroke risk factors as well as stroke subtypes in acute ischemic stroke patients.MethodsOne hundred eighty two acute cerebral infarction patients were included in this study. Brain magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
2
9
0
2
Order By: Relevance
“…Second, patients in the conventional cardiac monitoring cohort had a 2-fold higher prevalence of left atrial enlargement in the echocardiography compared with those in the ICM cohort. Taking into account the association of left atrial enlargement with underlying PAF, as uncovered in our analyses and highlighted in previous studies from our group 10 and other investigators, 24,25 we expect that the true incidence of PAF in the conventional cardiac monitoring cohort would be much higher than that uncovered in the ICM cohort. Third, the prevalence of valvular disease, which also has been independently associated with the probability of PAF detection in patients with cryptogenic stroke, 26,27 was also 3 times higher in patients receiving conventional cardiac monitoring compared to patients receiving ICM.…”
Section: Discussionsupporting
confidence: 62%
“…Second, patients in the conventional cardiac monitoring cohort had a 2-fold higher prevalence of left atrial enlargement in the echocardiography compared with those in the ICM cohort. Taking into account the association of left atrial enlargement with underlying PAF, as uncovered in our analyses and highlighted in previous studies from our group 10 and other investigators, 24,25 we expect that the true incidence of PAF in the conventional cardiac monitoring cohort would be much higher than that uncovered in the ICM cohort. Third, the prevalence of valvular disease, which also has been independently associated with the probability of PAF detection in patients with cryptogenic stroke, 26,27 was also 3 times higher in patients receiving conventional cardiac monitoring compared to patients receiving ICM.…”
Section: Discussionsupporting
confidence: 62%
“…Enlarged LA diameter (with addition of elevated thromboembolic risk in the CHADS 2 score) is a predictor of incident LA thrombi [ 21 ]. As a consequence, patients with LA enlargement are at higher risk of stroke, and majority of the stroke type occurring in this group are cardioembolic strokes [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, compared to other types of ischemic stroke, CE has a more abrupt onset with more severe conditions and a higher NIHSS score [ 16 , 17 ]. Third, a number of recent studies have confirmed that left atrial enlargement is correlated with stroke and can increase the risk of stroke [ 18 20 ], especially the risk of CE [ 21 ].As an important etiological factor in stroke of undetermined etiology [ 22 ]and an independent risk factor for CE and the recurrence of cryptogenic stroke [ 23 ],left atrial enlargement is associated with the stroke severity [ 24 ].Additionally, left atrial enlargement may lead to local thrombosis [ 25 ]. Jaroch et al found that a left atrial diameter greater than 51 mm was an independent risk factor for predicting thrombus in the left atrial appendage [ 26 ].…”
Section: Discussionmentioning
confidence: 99%